Social skills activities for special children - Mannix, Darlene (San Francisco : Jossey-Bass, 2009)
Contains more than 160 lessons and reproducible activity sheets designed to teach social skills to elementary school students with special needs, grouped in the categories of accepting rules and authority at school, relating to peers, and developing positive social skills.
"Over 160 ready-to-use lessons and worksheets to help children use social skills inside and outside the classroom"--Cover.
"Grades K-5"--Cover.
Professional
Professional
Bureche teacher resource library
Keywords: Developmentally disabled children -- United States -- Life skills guides; Developmentally disabled children -- Education (Secondary) -- United States; Life skills -- Study and teaching (Secondary) -- United States; Social skills -- Study and teaching (Secondary) -- United States; Developmentally disabled children -- Life skills guides; Developmentally disabled children -- Education; Life skills -- Study and teaching; Social skills -- Study and teaching